2016
DOI: 10.1176/appi.ajp.2015.15070921
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Modulation With Buprenorphine/Samidorphan as Adjunctive Treatment for Inadequate Response to Antidepressants: A Randomized Double-Blind Placebo-Controlled Trial

Abstract: The buprenorphine/samidorphan combination is a novel and promising candidate for treatment of major depressive disorder in patients who have an inadequate response to standard antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
157
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 40 publications
3
157
0
Order By: Relevance
“…Clinical evidence is supportive of this hypothesis; Alkermes have combined buprenorphine with the MOP antagonist samidorphan in a single sublingual tablet (ALKS5461) and in a 1:1 combination that provides KOP receptor antagonism and antagonism or extremely low stimulation at MOP receptors. ALKS5461 has been shown to have potential in the treatment of major depressive disorder [72,73] confirming the pre-clinical findings with buprenorphine-naltrexone and BU10119 [58,62].…”
Section: Mixed Kop/mop Antagonists Are Antidepressant In Animal Modelsmentioning
confidence: 53%
“…Clinical evidence is supportive of this hypothesis; Alkermes have combined buprenorphine with the MOP antagonist samidorphan in a single sublingual tablet (ALKS5461) and in a 1:1 combination that provides KOP receptor antagonism and antagonism or extremely low stimulation at MOP receptors. ALKS5461 has been shown to have potential in the treatment of major depressive disorder [72,73] confirming the pre-clinical findings with buprenorphine-naltrexone and BU10119 [58,62].…”
Section: Mixed Kop/mop Antagonists Are Antidepressant In Animal Modelsmentioning
confidence: 53%
“…Clinical and pre-clinical studies have demonstrated the efficacy of buprenorphine and its novel analogues in the pharmacotherapy Review Danuta Szkutnik-Fiedler of depression [3,[71][72][73][74][75][76]. Ahmadi et al [73] suggest that a single high-dose of buprenorphine provides a safe, speedy and straightforward means of depression, especially in patients who are opioid dependent.…”
Section: Buprenorphine and Its New Analoguesmentioning
confidence: 99%
“…Vital signs and weight were stable, and the executive function and learning improved. Fava et al [72] studied the antidepressant activity of a combination of buprenorphine and a μ-opioid antagonist, samidorphan in patients with major depression. They showed significantly greater antidepressant effects for this combination compared to the placebo and concluded that it might be a promising candidate for the treatment of a major depressive disorder in patients who have an inadequate response to standard antidepressants.…”
Section: Buprenorphine and Its New Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a multicenter, randomized, double-blind, placebo-controlled study have shown that the modulation of the opiate system may be a novel treatment approach for treatment-resistant depression. 18 …”
Section: New Drugs Opioidsmentioning
confidence: 99%